STRATEGI COPING ORANG TUA MURID PADA ANAK YANG MENGHADAPI KENDALA PEMBELAJARAN DARING DI MIN 15 MAGETAN - Mutiara Lutfiatul Hanifah; Dzinnun Hadi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
This research aimed to find out the application of student parents’ coping strategies in children who face online learning obstacles in MIN 15 Magetan. The research used a descriptive qualitative approach with sampling using purposive sampling techniques. The role of researchers was as a guidance implementer, data collector, and data analyzer. The subjects were 3 parents and 3 children who faced online learning obstacles. The data collection used was structured interviews, observations, and documentation studies. The results showed that there were several obstacles experienced by children when carrying out online learning, such as internet services, learning interests, and material understanding. While the obstacles experienced by parents were accompanying children, economic constraints, motivating children, understanding materials, and obstacles experienced by children when carrying out online learning. The obstacles experienced by children when facing online learning created their own pressure on parents and had their own negative impact on them. Parents performed different coping strategies to solve the problem in this way the parents succeed and got a positive impact.